Efficacy and safety of erythropoietin in patients with degenerative lumbar spinal stenosis undergoing multi-level lumbar interbody fusion: A case-control study - Wang, Dong; Liu, Ying; Cao, Shuang; Wu, Ying; Ni, Zhihao; Ning, Rende (Interdisciplinary neurosurgery : Advanced techniques and case management, 2025)
Study Design. Retrospective case-control study. To assess the efficacy of short-term and high-dose application of erythropoietin (EPO) in patients with degenerative lumbar spinal stenosis (DLSS) undergoing multi-level lumbar interbody fusion (LIF) by assessing mean transfusion volume, transfusion rate, hematologic parameters, postoperative complications, and length of stay. Summary of Background Data. It has been reported to confirm the efficacy and safety of EPO in major surgeries like neurosurgery, cardiac surgery, and orthopedics. Still, there was little information on the application of EPO in patients with DLSS undergoing multi-level LIF. Methods. 458 DLSS patients between January 2015 and December 2022 were selected and divided into EPO (group A), n = 112, and no EPO (group B), n = 105, according to treatment technique. Evaluation indexes included hemoglobin (Hb), hematocrit (Hct), red blood cells (RBC), postoperative complications, operative time, intraoperative bleeding, drainage volume, mean transfusion volume, transfusion rate, and length of stay. Results. The mean follow-up time was 21.7 months (18–24 months). Postoperative complications, surgical time, intraoperative bleeding, and drainage volume were not statistically different across groups. The Hb, Hct, and RBC values on postoperative days 1, 3, and 5 were significantly higher in group A than in B, and the difference was statistically significant (P < 0.05). The mean transfusion rate was significantly lower in group A than in B (P < 0.001). The mean transfusion volume was significantly lower in group A than in B (P < 0.001). The length of stay was significantly lower in group A than in B (P < 0.001). Conclusion. Short-term and high-dose perioperative EPO in DLSS patients undergoing multi-level LIF improves anemia-related hematologic parameters, reduces transfusion requirements, and shortens hospital stay without increasing deep vein thrombosis or wound infection.